Congenital Epulis: a clinical case presentation. Issue 2 (May 2014) - Sweeney, Kristie; Spurway, Jacqueline; Mein, Brendan; Magotti, Robert; Benzie, Ron; Challis, Daniel; Henry, Guy
Abstract: Congenital Epulis (CE) is a rare, benign tumour of the mucosa of the mouth in a neonate. It presents as an intraoral tumour and is rarely diagnosed prenatally. Complications include neonatal airway compromise, difficulty feeding and aesthetic considerations. Ultrasound is useful in aiding decisions regarding site, age, method of delivery and preparing parents and staff for the appearances of the tumour at birth. We present a case where CE was identified at 35 weeks gestational age during a routine third trimester prenatal ultrasound. The patient was scanned at a rural centre, referred to a tertiary institution for follow up and delivered at a specialist perinatal surgical centre, in preparation for neonatal surgery. The outcome was excellent and this case is a good example of multi‐centre cooperation.